Positioning Arabic Education Study Program Through Student Research Results 2011-2023 - Aflisia, Noza; Hazuar; Syohdikin, Syahrul; Abrilian, Rifqah Nabilah Ruby (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study aims to analyse the themes and methodologies of student research and to examine the positioning of the Arabic Education Study Program based on the mapping of student research outputs. The quality of student research significantly influences the development and reputation of the study program. This research employs a mixed-methods approach, combining qualitative and quantitative data derived from theses submitted by Arabic Education Study Program students at IAIN Curup between 2011 and 2023. Data collection was conducted through bibliographic surveys and document analysis. Data analysis followed Miles and Huberman’s framework, including data reduction, data display, and data verification, while credibility measures ensured data validity. The findings reveal that student research predominantly focuses on the development of Arabic language learning, primarily utilizing qualitative descriptive methods. The program has positioned itself as a centre for pedagogical development; however, further integration of linguistics and literature within Arabic language learning is recommended to enhance its scope.